2019
DOI: 10.3324/haematol.2018.210252
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of hepatitis B virus infection in patients with hematologic disorders

Abstract: Hepatitis B reactivation is the reappearance or rise of hepatitis B virus (HBV) DNA in patients with past or chronic HBV infection, usually occurring in the context of immunosuppression. HBV reactivation has been most commonly reported in patients with hematologic disorders, with potentially serious and life-threatening consequences. In this review, we discuss the basis and presentation of HBV reactivation, and risk factors in terms of the host, the virus and the immunosuppression regimen, including newer agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 79 publications
(89 reference statements)
1
67
0
1
Order By: Relevance
“…The small molecule Bruton's tyrosine kinase (BTK) inhibitors, for example, ibrutinib, have shown promising results in the treatment of lymphoma and chronic lymphocytic leukemia . These agents block B‐cell antigen receptor signaling, which prevents the growth of malignant B cells and induces apoptosis . Another mechanism of ibrutinib involves restoring the dysregulated T‐cell response that occurs in B‐cell malignancies by inhibiting the T helper 2 (Th2)‐polarized response and causing the compensatory activation of Th1 cells and cytotoxic T‐lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The small molecule Bruton's tyrosine kinase (BTK) inhibitors, for example, ibrutinib, have shown promising results in the treatment of lymphoma and chronic lymphocytic leukemia . These agents block B‐cell antigen receptor signaling, which prevents the growth of malignant B cells and induces apoptosis . Another mechanism of ibrutinib involves restoring the dysregulated T‐cell response that occurs in B‐cell malignancies by inhibiting the T helper 2 (Th2)‐polarized response and causing the compensatory activation of Th1 cells and cytotoxic T‐lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…HBV reactivation is a significant risk in patients who have a previous HBV infection and who require chemotherapy for hematological malignancies or are undergoing hematopoietic stem cell transplants (HSCT). [1][2][3][4][5][6] After the resolution of an acute HBV infection, small amounts of HBV DNA can remain in the liver, even if the DNA is no longer detectable in peripheral blood. The residual virus is controlled by innate immunity, but if the patient's immune system becomes suppressed (eg, during chemotherapy), the latent HBV in the hepatocytes begins to replicate rapidly.…”
Section: Patients With a Previous Or Chronic Hepatitis B Virus (Hbv) mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly many studies have shown that adriamycin-based chemotherapy and steroids have shown an increased incidence of reactivation of HBV. 11 Most of the reactivation occurs between the second and fourth cycle of chemotherapy. There are few studies which showed late reactivation of hepatitis B virus even after completion of chemotherapy, but in our study none of the patients got reactivated after 3 months of follow up, but a longer term of follow up must be needed.…”
Section: Discussionmentioning
confidence: 99%